Social welfare expenditures in the United States and the Nordic countries: 1900-2003 - National Bureau of Economic Research, Cambridge; Fishback, Price V. (Cambridge, MA, 2010)
"The extent of social expenditures in the U.S. and the Nordic Countries is compared in the early 1900s and again in the early 2000s. The common view that America spends much less on social welfare than the Nordic countries does not survive closer inspection when we consider the differences in the structures of social expenditures. The standard comparison examines gross social expenditures. After adjustments for direct and indirect taxes paid, the net social expenditures in the Nordic countries are much closer to American levels. Inclusion of mandatory and private social expenditures raises the American share of GDP devoted to social expenditures to rank among the middle of the Nordic countries. Per capita net public social expenditures in the U.S. rank behind only Sweden. Add in the private spending, and per capita spending in the U.S. is higher than in all of the Nordic countries. Finally, I document the enormous diversity across time and place in public social expenditures in the U.S. in the early 1900s and circa 1990. "